Analysis of the Use of The Complete Clause in the Daily Newspaper Titled 'Families of Victims of the Lingga Kencana Vocational School Accident' - Amelia Afriani; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
This research aims to study the format of the Detik News daily article for the 12 May 2024 edition. The clause form studied is a complete clause, where a complete clause is a grammatical unit consisting of a subject and a predicate, and has the potential to become a sentence, although not always. This complete clause can stand alone without needing to be combined with other clauses. The data collection technique used was by listening and taking notes in the daily newspaper Detik News entitled "Accident Victim's Family of Lingga Kencana Vocational School Call Old Bus - Not Well Maintained" on May 12 2024. The research data analyzed used qualitative descriptive analysis. Complete clauses based on their internal structure categories, the researchers found there were 26 complete clause form data in the daily newspaper detik news. Where the 26 data are divided into 21 complete regular clause data and 5 reversed complete clause data. However, the researchers found not only complete clauses in the daily detik news newspaper, but there were 4 pieces of data identified as incomplete clauses.